Assembly‐Induced Strong Circularly Polarized Luminescence of Spirocyclic Chiral Silver(I) Clusters - Wu, Han; He, Xin; Yang, Biao; Li, Cui‐Cui; Zhao, Liang (Angewandte Chemie International Edition, 2021)
Spirocyclic Ag9 clusters, as a new form of intrinsically chiral metal clusters, were constructed through vertex‐sharing of two in‐situ‐generated heteroaryl diide‐centered metal rings. Such core‐peripheral type clusters exhibit versatile photoluminescent and chiroptical behavior under different aggregation conditions. In contrast to a ligand‐based fluorescence emission in a diluted solution of the clusters, a solvent polarity‐caused assembly gives rise to new cluster‐based phosphorous luminescence owing to radiative mode switching and aggregation‐induced emission. Assembly of cluster enantiomers leads to micrometer‐long helical nanofibers, whose handedness is determined by absolute configuration of individual spirocyclic clusters. Benefiting from exciton couplings of helical arrangements of chelating ligands at molecular and microscopic levels, the assembled film of cluster enantiomers exhibits circularly polarized luminescence with a high anisotropy factor (0.16). Two spirocyclic Ag9 chiral clusters, as a new form of intrinsic chiral metal clusters, have been constructed. They show unique fluorescence‐to‐phosphorescence switching and aggregation‐induced emission under different aggregation conditions. The assembly of cluster enantiomers leads to micrometer‐long helical nanofibers and superior circularly polarized luminescence performance with a remarkably high anisotropy factor of 0.16.